2023
DOI: 10.1021/acs.macromol.3c00444
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of Polymerization-Induced Self-Assembly and Gelation During the Synthesis of Triblock Copolymers via Time-Resolved Small-Angle X-ray Scattering and Rheology

Abstract: The polymerization of solvophobic monomers from both ends of solvophilic polymers produces BAB triblock copolymers in solution. The self-assembly of the extending solvophobic blocks may lead to network formation and gelation. This process, referred to as polymerization-induced self-assembly (PISA) in triblock copolymers, is a topic of significant interest. The underlying mechanism, however, has been poorly understood in comparison to that of PISA in diblock copolymers. In this study, we used two independent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Over the past decade or so, polymerization-induced self-assembly (PISA) has become widely recognized as a powerful platform technology for the rational synthesis of a wide range of block copolymer nanoparticles. PISA involves the chain extension of a soluble block A in a suitable solvent using a monomer that forms an insoluble block B. Accordingly, in situ self-assembly occurs at some critical degree of polymerization (DP) for the second block to produce sterically stabilized nanoparticles, whereby the B block is located within the cores and the A block confers steric stabilization. , Various research groups have developed highly efficient one-pot syntheses for many PISA formulations. Moreover, PISA can be conducted using a wide range of solvents (including either water or oil) and the overall particle diameter can be systematically varied over a wide range in the case of kinetically trapped spheres. , This enables the convenient synthesis of libraries of sterically stabilized nanoparticles for model studies simply by adjusting the target DP for the insoluble core-forming block. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade or so, polymerization-induced self-assembly (PISA) has become widely recognized as a powerful platform technology for the rational synthesis of a wide range of block copolymer nanoparticles. PISA involves the chain extension of a soluble block A in a suitable solvent using a monomer that forms an insoluble block B. Accordingly, in situ self-assembly occurs at some critical degree of polymerization (DP) for the second block to produce sterically stabilized nanoparticles, whereby the B block is located within the cores and the A block confers steric stabilization. , Various research groups have developed highly efficient one-pot syntheses for many PISA formulations. Moreover, PISA can be conducted using a wide range of solvents (including either water or oil) and the overall particle diameter can be systematically varied over a wide range in the case of kinetically trapped spheres. , This enables the convenient synthesis of libraries of sterically stabilized nanoparticles for model studies simply by adjusting the target DP for the insoluble core-forming block. …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in situ self-assembly occurs at some critical degree of polymerization (DP) for the second block to produce sterically stabilized nanoparticles, whereby the B block is located within the cores and the A block confers steric stabilization. 39 , 40 Various research groups have developed highly efficient one-pot syntheses for many PISA formulations. 41 43 Moreover, PISA can be conducted using a wide range of solvents (including either water or oil) and the overall particle diameter can be systematically varied over a wide range in the case of kinetically trapped spheres.…”
Section: Introductionmentioning
confidence: 99%
“…This aligns with other studies that have shown enhancements in mechanical properties with the use of difunctional RAFT agents, which facilitate gelation or physical crosslinking in PISA nanostructures. 24–28…”
Section: Introductionmentioning
confidence: 99%
“…Micelles or vesicles are formed as polymerization proceeds. Nevertheless, fewer studies have been conducted on PISA of other architecture such as triblock copolymers than that of diblock copolymers. Recently, Zeng et al reported that a highly tough gel could be prepared via PISA of triblock copolymers; that is, from both terminals of polymer A, monomer B is polymerized to make a BAB triblock copolymer, where block B self-assembles with the polymerization. Furthermore, we previously studied the kinetics of the self-assembly and gelation process during the synthesis of BAB triblock copolymers …”
mentioning
confidence: 99%
“…The macro-CTAs were synthesized from commercially available star PEGs with hydroxy terminals and a CTA bearing a carboxy group through Steglich esterification (Scheme S1), and the synthesis and purification procedures were well established. ,, The full functionalization of PEG by CTA was confirmed using 1 H nuclear magnetic resonance (NMR) spectroscopy (Figure S1).…”
mentioning
confidence: 99%